Model Pembelajaran dalam Pendidikan Agama Katolik (PAK) pada Jenjang Pendidikan Sekolah Menengah Pertama (SMP) di Kota Pontianak - Gustaf Hariyanto; Florentinus Sutami; Kristina Laora; Aldi Alfrianza Sinulingga (Jurnal Penelitian Pendidikan Agama Katolik, 2023)
The diversity of paradigms and learning models is aimed to fulfill the needs of students. Learning materials need to be adapted according to the needs that are increasing from day to day. This study aims to explore and identify various teaching and learning models that are applied by Catholic Religious teachers at the junior high school level in Pontianak Municipality. It includes, first, the teaching and learning that are practiced by Catholic Religious Education (CRE) teachers; second, the various constraints experienced by CRE teachers in implementing the learning models; third, the extent of the students’ needs for CRE teaching and learning specifications. The study was conducted on 6 junior high schools, consisting of 5 state schools and 1 private Catholic. Primary data is collected by interview techniques. Through the interview technique, the researcher obtained information frominformants (teachers, students, and other related parties). Interviews were conducted in a semi-structured, assisted by an interview guide as a data collection tool without limiting the number of questions. Informants were selected purposively. In this study, Focus Group Discussion was also conducted as a forum for discussion and debriefing for CRE teachers in deepening their insight into the models. The study shows that the models are dominated by the cooperative model; while the constraints for the utilization of the models are the lack of facilities and the evaluation from the CRE teachers towards the learning models.